2019
DOI: 10.1007/978-3-030-04477-0_12
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles: Antimicrobial Applications and Its Prospects

Abstract: Nowadays, nanomaterials [NPs; size, 1-100 nm] have emerged as unique antimicrobial agents. Specially, several classes of antimicrobial NPs and nanosized carriers for antibiotic delivery have proven their efficacy for handling infectious diseases, including antibiotic-resistant ones, in vitro as well as in animal models, which can offer better therapy than classical drugs due to their high surface area-tovolume ratio, resulting in appearance of new mechanical, chemical, electrical, optical, magnetic, electro-op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 144 publications
0
20
0
Order By: Relevance
“…In this context, NPs are used as antimicrobial agents either for combatting resistance against antimicrobial drugs themselves or for the delivery of conventional antimicrobials. Their efficiency is generally related to the potential of NPs to penetrate and disrupt the membrane of the microbial cells via membrane-damaging abrasiveness; to decrease the permeability of the cell; to induce antimicrobial effects within the cells, e.g., reactive oxygen species (ROS) production, nucleic acids and protein interactions, enzyme inactivation, and the overexpression of efflux pumps; to release metal ions; and to hinder the formation of biofilms ( Figure 3 ) [ 20 , 29 , 41 , 62 , 63 , 64 , 65 ]. Moreover, NPs allow for an improved drug loading and delivery of both hydrophilic and lipophilic molecules as they are able to pass the reticuloendothelial system and internalize the antimicrobials [ 20 ].…”
Section: Inorganic Nanoparticles With Antimicrobial Propertiesmentioning
confidence: 99%
“…In this context, NPs are used as antimicrobial agents either for combatting resistance against antimicrobial drugs themselves or for the delivery of conventional antimicrobials. Their efficiency is generally related to the potential of NPs to penetrate and disrupt the membrane of the microbial cells via membrane-damaging abrasiveness; to decrease the permeability of the cell; to induce antimicrobial effects within the cells, e.g., reactive oxygen species (ROS) production, nucleic acids and protein interactions, enzyme inactivation, and the overexpression of efflux pumps; to release metal ions; and to hinder the formation of biofilms ( Figure 3 ) [ 20 , 29 , 41 , 62 , 63 , 64 , 65 ]. Moreover, NPs allow for an improved drug loading and delivery of both hydrophilic and lipophilic molecules as they are able to pass the reticuloendothelial system and internalize the antimicrobials [ 20 ].…”
Section: Inorganic Nanoparticles With Antimicrobial Propertiesmentioning
confidence: 99%
“…[252][253][254] Currently, there are no established global rules regarding the applications of food nanotechnology, however, the Organization for Economic Cooperation and Development (OECD) launched a sponsorship program for testing of nanomaterials in 2007, and the FDA issued four guidance documents on the use of nanotechnology in animal products, cosmetics, food, and other products in 2014-2015. 253 In the field of food nanotechnology, the approach of nanoparticles is considered to have the potential to be applied in various technologies, such as pesticides, 255 antimicrobial, 256 anti-solidification, 257 plant genetic engineering, 258 detection of foodborne pathogens, 259 food processing, 260 development of functional foods, 261 purification of drinking water, 262 extension of food preservation, 263 and texture improvement [252][253][254]264,265 (Figure 6). Surfactant-coated nanoparticles have been widely used in the field of food nanotechnology.…”
Section: Food Nanotechnologymentioning
confidence: 99%
“…One of the promising approaches for the smart delivery of antibacterial compounds is the use of nanocarriers ( Din et al, 2017 ). Several studies have demonstrated the advantage of antimicrobial NPs over free antimicrobial compounds ( Beyth et al, 2015 ; Wang Y. et al, 2017 ; Varier et al, 2019 ). Stability, solubility, and side effects are the important issues of pesticide use which are reduced by nanocarriers.…”
Section: Role Of Nanotechnology In Crop Protectionmentioning
confidence: 99%